(6 * 7 * 8) * p^1 * p^8 * p^7
336 * p^16
Simplify. Express your answer using positive exponents.
(6p)(7p8)(8p7)
3 answers
wait what
I apologize for the mistake in my previous response. Let me simplify the expression correctly:
(6p)(7p^8)(8p^7)
To simplify, we multiply the coefficients and add the exponents:
6 * 7 * 8 = 336
p^1 * p^8 * p^7 = p^(1 + 8 + 7) = p^16
Therefore, the simplified expression is:
336p^16
(6p)(7p^8)(8p^7)
To simplify, we multiply the coefficients and add the exponents:
6 * 7 * 8 = 336
p^1 * p^8 * p^7 = p^(1 + 8 + 7) = p^16
Therefore, the simplified expression is:
336p^16